Knowledge, attitudes and practices regarding environmental health services in Hospital Hill, Johannesburg Metropolitan Council, South Africa - Tjale, Lydia Mmapula (My University, 2012)
The purpose of this study was to establish the community’s knowledge, attitudes and practices regarding environmental health services (EHS) in the informal settlement of Hospital Hill. A qualitative, cross-sectional study was conducted using focus group discussions among study participants that satisfied the inclusion criteria. Each focus group discussion had varying duration ranging from one hour to one-and-half hours. The study revealed that there was lack of knowledge about EHS, with participants citing provision of water and sanitation facilities as the various roles that EHPs played. Participants’ attitude towards EHS and EHPs showed marked dissatisfaction due to their inaccessibility and unavailability. The lack of consultation, follow-up and community initiatives fuelled their negative attitudes towards EHS. Culture and beliefs, school dropout, human resources and lack of access to information discouraged the community from using EHS. A number of suggestions were made which revealed the community’s need and desire for EHS provision because environmental health problems were dealt with in different ways and these varied from one household to the other further signifying the need for a uniform approach was needed to deal with environmental health problems. The community of Hospital Hill was found to be experiencing discrimination evidenced by inexistence of EHS and consequent limited knowledge of EHS, negative attitudes and practices regarding EHS.
Thesis (MPH. (Health Measurement)) --University of Limpopo, 2012
Keywords: Attitudes; Disease prevention; Environmental health; Environmental health; Health services; Environmental protection